2019
DOI: 10.3390/md17060377
|View full text |Cite
|
Sign up to set email alerts
|

Probing Multi-Target Action of Phlorotannins as New Monoamine Oxidase Inhibitors and Dopaminergic Receptor Modulators with the Potential for Treatment of Neuronal Disorders

Abstract: Modulation of multiple protein targets with a single compound is essential for the effective treatment of central nervous system disorders. In our previous G protein-coupled receptor (GPCR) cell-based study, a selective human monoamine oxidase (hMAO)-A inhibitor, eckol, stimulated activity of dopamine D3 and D4 receptors. This result led to our interest in marine phlorotannin-mediated modulation of hMAO enzymes and related GPCRs in neuronal disorders. Here, we evaluate the multi-target effects of phloroglucino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…The study of Seong et al [238] focused on the action of phlorotannins in the mechanisms of anti-depressant and anti-Parkinson's disease. Dieckol and phlorofucofuroeckol-A (isolated from Ecklonia stolonifera) demonstrated high inhibition against the monoamine oxidases and demonstrated full agonists with high potency at the dopamine 3 and 4 receptors, proving that these compounds can have a multi-role intervention in the potential treatment of psychological disorders and Parkinson's disease.…”
Section: Phlorotanninsmentioning
confidence: 99%
“…The study of Seong et al [238] focused on the action of phlorotannins in the mechanisms of anti-depressant and anti-Parkinson's disease. Dieckol and phlorofucofuroeckol-A (isolated from Ecklonia stolonifera) demonstrated high inhibition against the monoamine oxidases and demonstrated full agonists with high potency at the dopamine 3 and 4 receptors, proving that these compounds can have a multi-role intervention in the potential treatment of psychological disorders and Parkinson's disease.…”
Section: Phlorotanninsmentioning
confidence: 99%
“…Enzyme kinetics and computational findings indicated that PFF-A noncompetitively interacted with h MAOs and acted allosterically. In a functional assay for GPCR screening, dieckol and PFF-A showed a multi-target combination of D 3 R/D 4 R agonism and D 1 /5HT 1A /NK 1 antagonism [ 140 ].…”
Section: Neuropharmacological Potentials Of Marine Algae and Theirmentioning
confidence: 99%
“…Phlorotannins, a natural polyphenol found abundantly in brown seaweeds (especially in the Ecklonia species), are known to have a diverse range of pharmacological activity. As neuroscience research progresses, the many neuroprotective effects of various phlorotannins are being reported, including inhibitory activity against enzymes linked to the pathogenesis of AD and PD [22,24,25,32], modulatory activity against G-protein coupled receptors related to neuronal diseases such as PD and psychological diseases [22,23], and free-radical scavenging activity [15]. Although some reports have indicated that phlorotannins have protective effects against the neurotoxicity of the Aβ 1-42 oligomer [32] or Aβ 25-35 peptides [33,34] in neuronal cell-lines, phlorotannins have not previously been studied as an inhibitor of Aβ self-aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that the molecular mechanism of the neuroprotective effects of eckol depended on monoamine oxidase-A inhibition and dopamine D 3 /D 4 receptor agonism [21,22]. Similarly, dieckol and phlorofucofuroeckol-A (PFFA) showed MAOs-A/B inhibition, D 3 R/D 4 R receptor agonism, and D 1 /5HT 1A /NK 1 receptor antagonism [23]. In addition, we discovered that the anti-AD activity of phlorotannins, including eckol, dioxinodehydroeckol, dieckol, and PFFA, occurred via inhibition of β-secretase and acetylcholinesterase [24,25].…”
Section: Introductionmentioning
confidence: 99%